Generation of tailored terahertz waves from monolithic integrated metamaterials onto spintronic terahertz emitters. (10th December 2020) - Liu, Yongshan; Bai, Zhongyang; Xu, Yong; Wu, Xiaojun; Sun, Yun; Li, Helin; Sun, Tong; Kong, RuRu; Pandey, Chandan; Kraft, Michael; Song, Qinglin; Zhao, Weisheng; et al.
Abstract: Recently emerging spintronic terahertz (THz) emitters, featuring many appreciable merits such as low-cost, high efficiency, ultrabroadband, and ease of integration, offer multifaceted capabilities not only in understanding the fundamental ultrafast magnetism physics but also for exploring multifarious practical applications. Integration of various flexible and tunable functions at the source such as polarization manipulation, amplitude tailoring, phase modulation, and radiation beam steering with the spintronic THz emitters and their derivatives can yield more compact and elegant devices. Here, we demonstrate a monolithic metamaterial integrated onto a W/CoFeB/Pt THz nanoemitter for a purpose-designed functionality of the electromagnetically induced transparency analog. Through elaborate engineering the asymmetry degree and geometric parameters of the metamaterial structure, we successfully verified the feasibility of monolithic modulations for the radiated THz waves. The integrated device was eventually compared with a set of stand-alone metamaterial positioning scenarios, and the negligible frequency difference between two of the positioning schemes further manifests almost an ideal realization of the proposed monolithic integrated metamaterial device with a spintronic THz emitter. We believe that such adaptable and scalable devices may make valuable contributions to the designable spintronic THz devices with pre-shaping THz waves and enable chip-scale spintronic THz optics, sensing, and imaging.